Aided phytoextraction of Cu, Pb, Zn, and As in copper-contaminated soils with tobacco and sunflower in crop rotation: Mobility and phytoavailability assessment. (February 2016) - Hattab-Hambli, Nour; Motelica-Heino, Mikael; Mench, Michel
Abstract: Copper-contaminated soils were managed with aided phytoextraction in 31 field plots at a former wood preservation site, using a single incorporation of compost (OM) and dolomitic limestone (DL) followed by a crop rotation with tobacco and sunflower. Six amended plots, with increasing total soil Cu, and one unamended plot were selected together with a control uncontaminated plot. The mobility and phytoavailability of Cu, Zn, Cr and As were investigated after 2 and 3 years in soil samples collected in these eight plots. Total Cu, Zn, Cr and As concentrations were determined in the soil pore water (SPW) and available soil Cu and Zn fractions by DGT. The Cu, Zn, Cr and As phytoavailability was characterized by growing dwarf beans on potted soils and determining the biomass of their plant parts and their foliar ionome. Total Cu concentrations in the SPW increased with total soil Cu. Total Cu, Zn, Cr and As concentrations in the SPW decreased in year 3 as compared to year 2, likely due to annual shoot removals by the plants and the lixiviation. Available soil Cu and Zn fractions also declined in year 3. The Cu, Zn, Cr and As phytoavailability, assessed by their concentration and mineral mass in the primary leaves of beans, was reduced in year 3. Highlights: Copper-contaminated soils were managed with assisted phytoextraction. The mobility and bioavailability of 4 trace elements were investigated in these soils. Trace elements phytoavailability was characterized by dwarf beans on potted soils. Phytoextraction significantly decreased the total concentrations of metals in the SPW. The phytoavailability of Cu increased with the total soil concentrations of Cu.